The Effect of Integrity, And Discipline on Quality of Work Life (Qwl) Government Internal Supervision Officers Republic of Indonesia Ministry of Law and Human Rights (International Journal of Scientific Research and Management (IJSRM), 2020)
The purpose of this research is to describe and analyze the influence of integrity and discipline of quality of work life (QWL). This research used a quantitative approach with survey methods. The samples of this research is the whole 132 government internal supervision officers Republic of Indonesia Ministry of Law and Human Rights which was performed randomly simple. The results showed that; (1) There is a direct positive influence integrity of the quality of work life (QWL); (2) There is no direct positive influence discipline of the quality of work life (QWL); (4) There is no direct positive influence transformational leadership of the discipline; (3) There is a direct positive influence integrity of the discipline; and (4) There is no indirect positive influence integrity of the quality of work life (QWL) through discipline. To improve the quality of work life (QWL), need to improve the integrity and discipline.